Random vibration in mechanical systems - Crandall, Stephen H (Academic Press, 1973)
Random Vibration in Mechanical Systems focuses on the fundamental facts and theories of random vibration in a form particularly applicable to mechanical engineers. The manuscript is a vital reference for mechanical engineers and researchers interested in random vibration in mechanical systems